2014
DOI: 10.1024/0036-7281/a000542
|View full text |Cite
|
Sign up to set email alerts
|

Mediaeval cattle from Bern (Switzerland): An archaeozoological, genetic and historical approach

Abstract: This study deals with genetic analyses of an assemblage of mediaeval (13th century) cattle metapodials from Bern that had previously been osteometrically examined regarding sex, shape and wither height. The results from the genetic sexing of these small (height 100 to 120 cm) cattle correlate well with the osteometric interpretations. Some few exceptions we interpreted as cows used as draft animals with stouter bones and thus osteometrically determined as males. Two morphologically different groups of cow meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“… Data genotyped for the black colour; C/C or C/T at site 296 and red and wild‐type T/T at site 296 (Svensson et al . , ; Telldahl et al . ). …”
Section: Summary Of Genotypic and Phenotypic Data Of European Ancientmentioning
confidence: 99%
“… Data genotyped for the black colour; C/C or C/T at site 296 and red and wild‐type T/T at site 296 (Svensson et al . , ; Telldahl et al . ). …”
Section: Summary Of Genotypic and Phenotypic Data Of European Ancientmentioning
confidence: 99%
“…The combined data from Fennoscandian bulls were divided into four temporal groups: Iron Age (n = 8 [ 25 ]), Medieval (n = 37 this study and [ 24 , 25 ]), Post-Medieval (n = 19 this study and [ 24 ]), and modern (n = 28 [ 22 ] and [ 11 ] as reported in [ 23 ]). To compare the temporal analyses in Fennoscandia to Central Europe, data from Medieval bulls (n = 14, [ 26 ]) from Switzerland was analysed together with data from modern Swiss breeds (Braunvieh, Ehringer, and Simmental, n = 39, [ 22 ] and [ 11 , 40 ] as reported in [ 23 ]).…”
Section: Methodsmentioning
confidence: 99%
“…The aim of this study was to explore temporal population variation by maternally and paternally inherited markers in cattle from the North East Baltic Sea region (N-EBSR), and to compare ancient populations with modern breeds. Haplotype data from 45 ancient mtDNA and 7 Y-chromosome samples was used together with contemporary data from 2094 mtDNA [ 10 , 11 , 15 , 16 , 20 ] and 1614 modern [ 22 24 ] and 71 ancient Y-chromosomes [ 24 26 ] samples. The data indicates clear changes in the N-EBSR cattle populations from late Bronze/Iron Age to modern times.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the spread of new generation sequencing in archaeogenetics to extend the studied region will always be hampered by the degree of DNA fragmentation in ancient samples. This process restricts the size of amplified and sequenced fragments even in the limited percent of archaeological finds still containing DNA under the environmental conditions of Central Europe [91]. The inevitable degradation also prevents the transfer of new technologies of long-range sequencing to the ancient samples, although this progress greatly simplifies targeted resequencing in extant populations.…”
Section: Challenges Of Genomic Approachesmentioning
confidence: 99%